2016
DOI: 10.1007/s10096-016-2714-9
|View full text |Cite
|
Sign up to set email alerts
|

Potential causative agents of acute gastroenteritis in households with preschool children: prevalence, risk factors, clinical relevance and household transmission

Abstract: Acute gastroenteritis (AGE) morbidity remains high amongst preschool children, posing a significant societal burden. Empirical data on AGE-causing agents is needed to gauge their clinical relevance and identify agent-specific targets for control. We assessed the prevalence, risk factors and association with symptoms for enteropathogens in households with preschool children. A monthly-repeated cross-sectional survey of enteropathogens in households with preschool children was performed. A parent-child pair per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
32
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 24 publications
(31 reference statements)
5
32
1
2
Order By: Relevance
“…Moreover, this study illustrates that D. fragilis is commonly acquired at an early age. These results are in line with the results of the recent Dutch studies (3,5) and with the observed peak in the positive proportion in clinical samples at the age of seven in Denmark (9).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Moreover, this study illustrates that D. fragilis is commonly acquired at an early age. These results are in line with the results of the recent Dutch studies (3,5) and with the observed peak in the positive proportion in clinical samples at the age of seven in Denmark (9).…”
Section: Discussionsupporting
confidence: 92%
“…Because few children had several siblings, the increase in odds of testing positive and highly positive with number of siblings should be interpreted cautiously. However, similar results were obtained in the recent Dutch study (5). The epidemiological role of siblings remains unknown, as the transmission routes of D. fragilis need clarification (15).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…A study of children in the Netherlands found an association between exposure to livestock and detection of norovirus in stool (23). Finally, although the association in our analyzed cohort was not significant, we were surprised to find that having an indoor toilet tended to be associated with norovirus diarrhoea.…”
Section: Discussionmentioning
confidence: 99%